Unconventional phenomena in a transverse Ising quadrangular nanowire. (July 2017) - Kaneyoshi, T.
Abstract: The magnetic properties (phase diagrams and magnetizations) of a transverse Ising quadrangular nanowire are investigated for the two cases, using the effective field theory with correlations. The first case is that the transverse field ΩS at the surface shell is selected as a finite value and the transverse field ΩC in the core is fixed at ΩC =0.0. The second case is that ΩC =0.0 and the value of ΩS is changed. Many unconventional phenomena have been found for them; such as the reentrant phenomena, the appearance of a compensation point and the unexpected behaviors of a critical transverse field at which the transition temperature reduces to zero. The temperature-induced magnetization sign reverse in an applied magnetic field is also investigated. Highlights: The phase diagrams and magnetizations of a transverse Ising quadrangular nanowire are examined for the two cases. The transverse field ΩS at the surface shell is changed and the transverse field ΩC in the core is fixed at ΩC =0.0. The value of ΩC is fixed at ΩC =0.0 and the value of ΩS is changed. The effective-field theory with correlations has been used. Many unconventional phenomena have been found for them, such as the reentrant phenomena.